Putusan Mahkamah Konstitusi Nomor 55/PUU-XVIII/2020 : Menciderai Keadilan Bagi Peserta Pemilu - Athari Farhani; Faiqah Nur Azizah (UIN Syarif Hidayatullah Jakarta, 2022)
The decision of the Constitutional Court Number 55/PUU-XVIII/2020 in its ruling gave special treatment to political parties that passed the Parliamentary Threshold in 2019 not to need to carry out factual verification, but only with administrative verification. However, this requirement does not apply to political parties that do not pass the Perlementary Threshold in 2019. Even though political dynamics occur very dynamically, so that the stages of administrative verification and factual verification are deemed necessary for all parties. The existence of this decision seems discriminatory and injures the sense of justice and democratic principles in general elections.